A Metal-Insulator-Metal Deep Subwavelength Cavity Based on Cutoff Frequency Modulation - Kihwan Moon; Tae-Woo Lee; Young Jin Lee; Soon-Hong Kwon (Applied Sciences, 2017)
We propose a plasmonic cavity using the cutoff frequency of a metal-insulator-metal (MIM) first-order waveguide mode, which has a deep subwavelength physical size of 240 × 210 × 10 (nm3) = 0.00013 λ03. The cutoff frequency is a unique property of the first-order waveguide mode and provides an effective mode gap mirror. The cutoff frequency has strong dependence on a variety of parameters including the waveguide width, insulator thickness, and insulator index. We suggest new plasmon cavities using three types of cutoff frequency modulations. The light can be confined in the cavity photonically, which is based on the spatial change of the cutoff frequency. Furthermore, we analyze cavity loss by investigating the metallic absorption, radiation, and waveguide coupling loss; the radiation loss of the higher-order cavity mode can be suppressed by multipole cancellation.